From Availability to Accessibility. Vaccination Proximity in a Social Clinic in Palermo - Vallerani, Sara (PARTECIPAZIONE E CONFLITTO, 2023)
The present paper explores protests and initiatives in the vaccination field carried out by organisations developed within social movements, specifically focusing on the collective social actors involved in the Covid-19 vaccination campaign by proposing differentiated intervention strategies to ensure equity in access to the vaccine. The case study is the social clinic of Borgovecchio (Palermo) which developed a vaccination centre that responds to the principles of Primary Health Care (accessible, proactive and inspired by a spirit of ’proximity’). The social clinic is located in the community centre Anomalia. Data collection was carried out through observation and semi-structured interviews. The so-called ’proximity vaccine centre’ project results from the radical criticism of the official vaccination campaign. The paper analyses the distinctive elements between this grassroots initiative and the official vaccination campaign, the initiative’s guiding principles and goals, the organisational aspects and the ambivalences of the relationship with institutions. The results suggest that the primary goal of the "grassroots vaccine centre" was to safeguard the inhabitants of the district through a ’re-territorialisation’ of the intervention and the valorisation of different elements such as relation, spatial proximity and "trust". Additionally, the involvement of the social clinic in the vaccination campaigns represents an unprecedented collaboration between the National Health System and an informal organisation. Consequently, this case study represents a privileged observation point for analysing the relationships and conflicts between a self-organised experience and governmental institutions. Finally, this contribution suggests a broad reflection on the processes of politicisation in the healthcare domain and on the risk that initiatives implemented in an emergency logic produce or reinforce further inequalities in access to services.